Brainstem involvement in subacute sclerosing panencephalitis - Yaramiş, Ahmet; Taşkesen, Mustafa (The Turkish Journal of Pediatrics, 2010)
Subacute sclerosing panencephalitis (SSPE), which usually develops 2-10 years after measles infection, is a progressive neurologic disorder with an insidious onset. The neurologic dysfunctions associated with SSPE include generalized myoclonic jerks and seizure activity, and progression of the disease usually results in coma and death within one to two years after onset. Most of the cerebral lesions in SSPE are observed in the periventricular and subcortical white matter. Brainstem involvement in SSPE is very rare. In this paper, we report two cases with brainstem involvement in SSPE that was accompanied by other intracranial lesions with magnetic resonance imaging (MRI). These two patients died in a short time. Thus, brainstem involvement should be considered in patients with SSPE.